Bicycle Use for Transport in an Australian and a Belgian City: Associations with Built-Environment Attributes - Owen, Neville; De De Bourdeaudhuij, Ilse; Sugiyama, Takemi; Leslie, Eva; Cerin, Ester; Van Van Dyck, Delfien; Bauman, Adrian (Journal of urban health, 2010)
The walkability attributes of neighborhood environments (residential density, land use mixture, and connectedness of streets) have been found to be associated with higher rates of walking. However, relatively less is known about the associations of walkability attributes with bicycle use for transport. We examined the relationships between adults' bicycle use for transport and measures of neighborhood walkability in two settings: an Australian city (Adelaide) with low rates of bicycle use and a Belgian city (Ghent) with high rates of bicycle use. A total of 2,159 and 382 participants were recruited in Adelaide and Ghent, respectively. A walkability index was derived from objectively measured data in Adelaide, while a similar index was derived from perceived measures in Ghent. Logistic regression models were employed to examine associations of bicycle use with different levels of walkability. There were higher rates of bicycle ownership for Ghent compared to Adelaide participants (96% versus 61%), and there was a higher prevalence of bicycle use for transport for Ghent compared to Adelaide participants (50% vs. 14%). Despite the large differences in bicycle ownership and use, living in a high-walkable neighborhood was associated with significantly higher odds of bicycle use for transport in both cities, after adjusting for relevant confounding factors. Built-environment innovations that are increasingly being advocated by health authorities and transport planners, primarily to promote higher rates of walking for transport, should also impact positively on bicycle use.